Some dance and health books Book and video reviews - Glasstone, Richard (Dance Books Ltd., Alton,Hampshire (UK), 1998)
Dance and health books. Pilates video.
Body Control: The Pilates Way. Lynne Robinson &Gordon Thomson, Boxtree, 1997. Warm Up: Anatomy as a Master Image. Tuth and Gus Solomons, Dance Videos, 1997. The Vitality Plan. Deborah Bull, Dorling Kindersley, 1998. Staging Dance. Susan Cooper, A & C Black, 1998.